2019
DOI: 10.1002/hep.30285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Undetectable Vaccine‐Induced Immunity Against Hepatitis B Virus in US Adults at High Risk for Infection

Abstract: In 2015, the Centers for Disease Control and Prevention reported a substantial increase in the number of acute hepatitis B virus (HBV) infections in the United States. Although national guidelines recommend vaccination of adults at high risk for HBV infection, the prevalence of undetectable immunity (i.e., susceptibility) in this population remains unknown. In this study, we analyzed a nationally representative sample using the National Health and Nutrition Examination Survey to evaluate the prevalence, trend,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…However, despite the progress of vaccination coverage in the U.S., we found that more than 70% of the general adult population did not have serological evidence of vaccine‐mediated immunity. Our results are also in line with recent reports that approximately 64 million U.S. persons considered to be high risk by the Centers for Disease Control and Prevention criteria still had undetectable immunity against HBV in 2013‐2014 (69.4%), suggesting that although these efforts are effective, efforts may need to be specifically targeted to those at the highest risk for HBV (foreign born, non‐Hispanic Asian, adults with high‐risk behaviors) to bring about a substantial decrease in HBV exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, despite the progress of vaccination coverage in the U.S., we found that more than 70% of the general adult population did not have serological evidence of vaccine‐mediated immunity. Our results are also in line with recent reports that approximately 64 million U.S. persons considered to be high risk by the Centers for Disease Control and Prevention criteria still had undetectable immunity against HBV in 2013‐2014 (69.4%), suggesting that although these efforts are effective, efforts may need to be specifically targeted to those at the highest risk for HBV (foreign born, non‐Hispanic Asian, adults with high‐risk behaviors) to bring about a substantial decrease in HBV exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Among persons with HBV infection, awareness of having a liver condition and treatment rate were low. To achieve the goal of the Department of Health and Human Services to increase the diagnosis rate from one‐third to two‐thirds of persons with chronic HBV by 2020 and the elimination of HBV by 2030, more effort is needed to improve screening and disease awareness among providers and high‐risk groups for HBV infection so as to provide vaccination to those who remain unvaccinated and treatment to those who require treatment …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of immunity is also low among adults considered high risk for HBV in the U.S, and approximately 64 million high‐risk adults did not have detectable anti‐HBs in 2015‐2016. In this study, older age and lower socioeconomic status were significant risk factors for having undetectable immunity 12 . Therefore, more efforts to identify and implement HBV vaccination for high‐risk adults (Figure 4) are needed, especially in older and more resource‐limited populations.…”
Section: Gaps In Hbv Vaccination and Preventionmentioning
confidence: 83%
“…Those considered most at risk for acute HBV infection are people who inject drugs (PWIDs) and those with multiple sexual partners which include male‐to‐male sexual encounters 11 . Unfortunately, there are still about 60 million adult Americans considered high risk for HBV infection by the Center for Disease and Controls (CDC) lacking protective immunity 12 …”
Section: Introductionmentioning
confidence: 99%
“…[39] Therefore, informed consents, more intensive HBV prophylaxis and post-transplant monitoring were still in great need for those willing to accept HBsAg + kidneys. [40]…”
Section: Discussionmentioning
confidence: 99%